2010
DOI: 10.1111/j.1525-1594.2009.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training During Hemodialysis Reduces Blood Pressure and Increases Physical Functioning and Quality of Life

Abstract: Hypertension and cardiovascular diseases are highly prevalent in hemodialysis patients and are associated with the reduction of physical functioning and quality of life. We evaluated the effects of supervised aerobic exercise training on physical functioning, blood pressure, quality of life, and laboratory data in hemodialysis patients. Fourteen patients were evaluated at the beginning and after 12 weeks of stretching exercises (control phase) and at the end of 12 weeks of aerobic exercise training performed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 25 publications
7
31
0
6
Order By: Relevance
“…After intervention period, the 6MWT distance was significantly increased in the intervention group compared with the control group, indicating that the endurance-resistance program increased physical functioning in HD patients. These findings are in agreement with previous reports on exercise in HD patients (Parsons et al, 2006; Reboredo Mde et al, 2010). For instance, Reboredo Mde et al (2010) showed that 3 months of aerobic exercise training performed during hemodialysis sessions increased significantly by 9% the 6MWT distance in 14 HD patients.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…After intervention period, the 6MWT distance was significantly increased in the intervention group compared with the control group, indicating that the endurance-resistance program increased physical functioning in HD patients. These findings are in agreement with previous reports on exercise in HD patients (Parsons et al, 2006; Reboredo Mde et al, 2010). For instance, Reboredo Mde et al (2010) showed that 3 months of aerobic exercise training performed during hemodialysis sessions increased significantly by 9% the 6MWT distance in 14 HD patients.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in agreement with previous reports on exercise in HD patients (Parsons et al, 2006; Reboredo Mde et al, 2010). For instance, Reboredo Mde et al (2010) showed that 3 months of aerobic exercise training performed during hemodialysis sessions increased significantly by 9% the 6MWT distance in 14 HD patients. In another study, Parsons et al (2006) showed that 5 months of endurance exercise training during dialysis in 13 HD patients were associated with an increase of 14% in the 6MWT distance.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, studies have demonstrated that these factors can be influenced by a training program (resistance exercises, aerobic training and flexibility) which can improve the health-related quality of life of HD patients. (12,34,35) The training program should not be neglected in health care because it has a positive effect on mental health and well-being, reducing depression and anxiety and improving cognitive functioning (36) . Some aspects about the relevance of this study should be highlighted.…”
Section: Discussionmentioning
confidence: 99%